Peptide chain release factor DIG8 regulates plant growth by affecting ROS-mediated sugar transportation in Arabidopsis thaliana - Zhang, Xiangxiang; Han, Yuliang; Han, Xiao; Zhang, Siqi; Xiong, Liming; Chen, Tao (Frontiers in Plant Science, 2023)
Chloroplasts have important roles in photosynthesis, stress sensing and retrograde signaling. However, the relationship between chloroplast peptide chain release factor and ROS-mediated plant growth is still unclear. Here we identified DIG8, a chloroplast localized peptide chain release factor, which is essential for separation of newly translated peptides from ribosomes. The dig8 mutant has few lateral roots and a pale green leaf phenotype. By map-based cloning, the DIG8 gene was located on AT3G62910, with a point mutation leading to amino acid substitution in functional release factor domain. The DIG8 protein was characterized locating in chloroplast by co-localization with plastid marker and interacting with ribosome-related proteins by yeast-two-hybrid and BiFC. Abnormal thylakoid stack formation and chloroplast dysfunction in the dig8 mutant caused increased ROS activity leading to callose deposition and lower PD permeability. A local sugar supplement partially alleviated the growth retardation phenotype of the mutant. These findings shed light on chloroplast peptide chain release factor-affected plant growth by ROS stress.